The Role and Effectiveness of Accounting Information Systems in Modern Organizations: A Comprehensive Analysis - Mukhsin, Mukhsin; Junaedi, Achmad Tavip; Suhardjo, Suhardjo; Renaldo, Nicholas; Prayetno, Muhammad Pringgo (Institut Bisnis dan Teknologi Pelita Indonesia, 2024)
In today's dynamic business environment, the accuracy and efficiency of financial data processing are paramount for organizational success. Accounting Information Systems (AIS) have emerged as critical tools that integrate traditional accounting practices with advanced information technology, offering businesses a structured mechanism for collecting, processing, and reporting financial information. This study examines the significance of AIS by reviewing existing literature and employing a mixed-methods approach, including surveys, interviews, and case studies, to assess its effectiveness. The findings indicate that while AIS significantly improves financial reporting accuracy, efficiency, and decision-making, its successful implementation depends on overcoming challenges such as high initial costs, employee resistance, and the need for continuous training. The study concludes by offering practical recommendations for optimizing AIS implementation and suggests areas for ongoing system evaluation and improvement.